2010
DOI: 10.1177/104063871002200113
|View full text |Cite
|
Sign up to set email alerts
|

Development of One-Step Real-Time Reverse Transcription Polymerase Chain Reaction Assays for Rapid Detection of Porcine Group C Rotaviruses

Abstract: Abstract. Although the widespread occurrence of porcine group C rotaviruses (GCRV) is assumed, precise prevalence remains largely unknown because of the absence of reliable, specific, and rapid diagnostic methods. To detect and quantify porcine GCRV, the authors evaluated and optimized SYBR Green and TaqMan real-time reverse transcription polymerase chain reaction (RT-PCR) assays and applied them to 108 piglet fecal samples. Using serially diluted standard RNA transcripts of porcine GCRV VP6 gene, both SYBR Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…Similar high prevalence of ARoVs has been reported from Thailand (22.3%) (Khamrin et al, 2007), Brazil (35.3%) (Rácz et al, 2000), and South Korea (38%) (Chun et al, 2010); whereas other countries have reported much lower prevalence in swine populations (e.g. 4% in Germany; 9.2% in Canada; 3% in Argentina) (Wieler et al, 2001; Morin et al, 1983; Parra et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Similar high prevalence of ARoVs has been reported from Thailand (22.3%) (Khamrin et al, 2007), Brazil (35.3%) (Rácz et al, 2000), and South Korea (38%) (Chun et al, 2010); whereas other countries have reported much lower prevalence in swine populations (e.g. 4% in Germany; 9.2% in Canada; 3% in Argentina) (Wieler et al, 2001; Morin et al, 1983; Parra et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…In our previous reports using RT-nested PCR and real-time PCR targeting the VP6 gene of RVCs (Chun et al, 2010;Jeong et al, 2009), porcine RVC infections were found to be widespread in Korean piglets with diarrhea. However, the VP7, VP4 or VP6 genotypes of the infecting Korean porcine RVCs remained largely unknown.…”
Section: Introductionmentioning
confidence: 93%
“…Currently, polymerase chain reaction (PCR)-based methods have been proven convenient and highly sensitive for detecting porcine diarrhea-associated viruses [20,21]. Of them real-time SYBR Green PCR method that combines conventional PCR and fluorescent signal detection with advantages of high sensitivity, good repeatability, and intuitive results is widely used for epidemiological investigation and pathogen identification [22][23][24]. Moreover, the closed-tube detection of SYBR Green-based real-time PCR assay can effectively prevent aerosol pollution and reduce the incidence of false positives.…”
Section: Introductionmentioning
confidence: 99%